2002
DOI: 10.1017/s002531540200560x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of viruses responsible for the demise of an Emiliania huxleyi bloom in the English Channel

Abstract: This study used analytical £ow cytometry (AFC) to monitor the abundance of phytoplankton, coccoliths, bacteria and viruses in a transect that crossed a high re£ectance area in the western English Channel. The high re£ectance area, observed by satellite, was caused by the demise of an Emiliania huxleyi bloom. Water samples were collected from depth pro¢les at four stations, one station outside and three stations inside the high re£ectance area. Plots of transect data revealed very obvious di¡erences between Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
162
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 25 publications
4
162
0
Order By: Relevance
“…It forms massive annual spring blooms that are detectable from space by satellites and affects global climate and biogeochemical cycles of carbon and sulfur (Hatton et al, 2004;Rost and Riebesell, 2004;Tyrrell and Merico, 2004). E. huxleyi blooms are routinely infected and terminated by specific giant double-stranded DNA coccolithoviruses (Phycodnaviridae) (Bratbak et al, 1993;Brussaard et al, 1996;Schroeder et al, 2002;Wilson et al, 2002;Lehahn et al, 2014), the E. huxleyi virus (EhV), which is part of the nucleocytoplasmic large DNA virus (Asfarviridae, Ascoviridae, Iridoviridae, Marseilleviridae, Megaviridae, Mimiviridae, Pandoraviridae, Phycodnaviridae, Pithoviridae and Poxviridae) clade. EhV encodes for an almost complete de-novo biosynthetic pathway for ceramide (Wilson et al, 2005), a sphingolipid known to induce apoptosis in animals and plants (Pettus et al, 2002;Liang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It forms massive annual spring blooms that are detectable from space by satellites and affects global climate and biogeochemical cycles of carbon and sulfur (Hatton et al, 2004;Rost and Riebesell, 2004;Tyrrell and Merico, 2004). E. huxleyi blooms are routinely infected and terminated by specific giant double-stranded DNA coccolithoviruses (Phycodnaviridae) (Bratbak et al, 1993;Brussaard et al, 1996;Schroeder et al, 2002;Wilson et al, 2002;Lehahn et al, 2014), the E. huxleyi virus (EhV), which is part of the nucleocytoplasmic large DNA virus (Asfarviridae, Ascoviridae, Iridoviridae, Marseilleviridae, Megaviridae, Mimiviridae, Pandoraviridae, Phycodnaviridae, Pithoviridae and Poxviridae) clade. EhV encodes for an almost complete de-novo biosynthetic pathway for ceramide (Wilson et al, 2005), a sphingolipid known to induce apoptosis in animals and plants (Pettus et al, 2002;Liang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Their high abundance and obligately parasitic lifestyle allow viruses to exert top-down control of cellular organism populations, which is illustrated most dramatically through the implication that viruses are involved in the termination of some algal blooms (e.g., Bratbak et al, 1993;Tarutani et al, 2000;Wilson et al, 2002;Brussaard et al, 2005: Gobler et al, 2007Tomaru et al, 2007). More subtly, viruses contribute to the mortality of bacteria, phytoplankton and higher trophic levels of the aquatic food web (Proctor and Fuhrman, 1990;Suttle, 1994;Baudoux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the role of viruses in controlling the bloom development of E. huxleyi (Bratbak et al, 1993, Brussaard et al, 1996, Castberg et al, 2001, Jaquet et al, 2002, Wilson et al, 1998, 2002a, 2002b. It became evident from these investigations that viruses are intrinsically linked to the decline of E. huxleyi blooms.…”
Section: Introductionmentioning
confidence: 99%
“…A range of different viruses that infect E. huxleyi (EhV) were isolated from the English Channel and off the coast of Bergen, Norway (Castberg et al, 2002, Wilson et al, 2002b and were analysed for their phylogeny (Schroeder et al, 2002), ecological successions in mesocosm experiment (Schroeder et al, 2003) and genome structure (EhV-86) (Allen et al, 2006, Wilson et al, 2005. Characterization of their sequences revealed that the E. huxleyi viruses are large double-stranded DNA viruses with genomes approximately 410 kbp in size and that they belong to a new virus genus termed Coccolithovirus based on the phylogeny of their DNA-polymerase gene (Schroeder et al, 2002).…”
Section: Introductionmentioning
confidence: 99%